A comparative study on characteristics and leaching toxicity of fluidized bed and grate furnace MSWI fly ash. (1st March 2022) - Fan, Chengcheng; Wang, Baomin; Ai, Hongmei; Liu, Ze
Abstract: Grate furnace and fluidized bed are the most widely used technologies for municipal solid waste incineration (MSWI), which play significant roles in characteristics of MSWI fly ash. A comparative study of the physicochemical characteristics, microstructure morphology and leaching toxicity of fluidized bed and grate furnace MSWI fly ash was conducted in this work, and some resource utilization and disposal treatments were proposed. Results showed that calcium salt and chlorine salt formed the dominant components of MSWI fly ash. CaO–SiO2 –Al2 O3 ternary system indicated that MSWI fly ash had potential pozzolanic activity, similar to coal fly ash and blast furnace slag. The total Pb, Cd and Zn contents in fluidized bed MSWI fly ash was only 1/2, 1/3 and 2/3 of grate furnace MSWI fly ash, respectively. Leachability of Pb in MSWI fly ash collected from Dalian, Shanghai, Zhuji and Hangzhou was 4.25 mg/L, 3.83 mg/L, 3.84 mg/L and 3.68 mg/L, 28.3, 25.5, 25.6 and 24.5 times as much as the national standard limitation (GB16889-2008), respectively. However, grate furnace MSWI fly ash with high chloride and unstable chemical speciation distribution of heavy metals would pose more environmental risk toits immobilization and disposal. Fluidized bed fly ash is a promising candidate for preparing the Portland cement clinker, microcrystalline glass and ceramics due to its high Si and Al content. Grate furnace MSWI fly ash is more appropriate for Alinite cement preparation because of high chloride content. Highlights: Comparative study on fluidized bed and grate furnace MSWI fly ash was conducted. Comparative CaO–SiO2 –Al2 O3 ternary system of several materials was created. Leachability of Pb in MSWI fly ash far exceeded the landfill standard thresholds. More environmental risk was found in grate furnace MSWI fly ash.